Pengembangan Sistem Informasi Manajemen Distribusi Pupuk Berbasis Web (Studi Kasus : PT. Petrokopindo Cipta Selaras) - Fahrir Rijal Fahmi Maulana; Achmad Arwan; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. Petrokopindo Cipta Selaras (PCS) is a subsidiary of PT. Petrochemical Gresik. PCS is engaged in services, one of which is fertilizer distribution. The problem that often occurs in the process of fertilizer distribution is that Operational Employees who work in the field experience obstacles in reporting their duties, this is because the location is quite far (an average of more than 5 km) from the Head of Division. Because of this, the Head of Sector has difficulty monitoring ongoing tasks. In the end, all of that impacts on the Accounting Field that cannot receive the results of reports from each field quickly and efficiently, so that the Accounting Field cannot freely anticipate losses that occur suddenly amid the ongoing distribution process. Based on the problems that have been explained, then developed a distribution management information system to overcome these problems. Development is carried out with an object oriented approach and the waterfall method. The flow of research carried out is the study of literature, needs analysis, design, implementation, testing, drawing conclusions and suggestions. In the needs analysis phase it produces 40 functional needs and one non-functional requirement. At the design stage, three types of design are produced, namely architectural design, component design, and database structure design. The implementation phase is done in PHP and Codeigniter framework. At the test stage unit testing and integration with the white box approach are 100% valid. Validation testing using the black box approach yields 100% valid. Compatibility testing performed on the Google Chrome and Firefox browsers yields 100% valid.